FRI0129 DEVELOPMENT OF A PREDICTION MODEL FOR MAXIMUM METHOTREXATE (MTX) DOSE WITHOUT HEPATOTOXICITY USING AN INDEX OF ERYTHROCYTE MTX-POLYGLUTAMATE (MTXPG) LEVELS SPECULATED BY CLINICAL AND GENETIC MARKERS. (2nd June 2020) - Kumagai, S.; Takahashi, S.; Takahashi, M.; Saito, T.; Yoshida, K.; Katayama, M.; Mukohara, S.; Amano, N.; Onishi, A.; Shinohara, M.; Hatachi, S.
Abstract : Background: MTX is transported into cells and retained long after polyglutamation. MTXPG level can predict response and possibly adverse effects of MTX. We reported erythrocyte MTXPG concentrations efficiently discriminated patients with and without hepatotoxicity 1 . We also developed genetic and clinical prediction models for efficacy and hepatotoxicity of MTX 2 . In the present study, we firstly investigated the effects of clinical and secondly genetic variables on the concentration of total MTXPG and determined oral maximum MTX dose without hepatotoxicity using these variables. Objectives: To develop a prediction model for maximum MTX dose without hepatotoxicity. Methods: Concentrations of erythrocyte MTX-PG (PG1 to PG4) were detected by LC-MS/MS and calculated total MTXPG as sum of them. MTX-PGn levels were measured in 265 RA patients including 40 patients with elevated AST or ALT (≥ 60 U/L; 1.5 times of upper limits) and the 6 SNPs of 6 gens related to MTXPG metabolism were identified by RT-PCR. Results: Total concentrations of MTXPG were 141.3 ± 86.5 and 87.6 ± 47.8 nmol/L (mean±SD) in 40 RA patients with hepatotoxicity and 225 patients without, respectively (p<0.0001). By ROC analysis, the two groups were most efficiently discriminated with cutoff concentration of 100.0 nmol/L (AUC 0.731). Next, genetic and clinical model to speculate the MTXPG concentration was established by multivariate analysis using 4 clinical and 3 genetic variables which were selected from 20 clinical and 6 genetic variables by univariate analysis (p<0.1). Finally, a speculation model for MTXPG concentration by 4 clinical variables (MTX dose, BMI, RBC count, and creatinine) and one genetic variable (GGH c.452C>T) was developed (Figure). When MTXPG concentration of 100 nmol/L was applied to the model, maximum MTX dose without hepatotoxicity was calculated for each patient as MTX dose (mg) = {100 (MTXPG) – 96 + 1.7*BMI + 28*RBC - 120*creatinine - 19.3*GGH(C/T)} / 7.7 . Real dose of oral MTX exceeded the calculated dose in 23 of 40 patients (57.5%) with hepatotoxicity, whereas it exceeded in 95 of 223 patients (42.6%) without hepatotoxicity (OR 1.82, p=0.081). Conclusion: Maximum MTX dose without hepatotoxicity was speculated by several clinical and genetic markers without measurement of erythrocyte MTX-PG concentrations. References: [1]Takahashi M, et al: Clinical Pathology (Rinsho Byori), 67:433-442, 2019. [2]Onishi A, et al: The Pharmacogenomics J, doi.org/10.1038/s41397-019-0134-9, 2019 Disclosure of Interests: Shunichi Kumagai Grant/research support from: Astellas, Chugai, Mitsubishi Tanabe Co.Ltds, Consultant of: Sysmex Co.Ltd, Speakers bureau: many companies, Soshi Takahashi: None declared, Miho Takahashi: None declared, Toshiharu Saito: None declared, Katsuyuki Yoshida: None declared, Motoko Katayama: None declared, Saki Mukohara: None declared, Norihiko Amano: None declared, Akira Onishi Speakers bureau: AO received a speaker fee from Chugai, Ono Pharmaceutical, Eli Lilly, Mitsubishi-Tanabe, Asahi-Kasei, and Takeda, Masakazu Shinohara: None declared, Saori Hatachi: None declared